Group of Homonyms “Kolymka” (Word-Formation and Functional Aspects) - A. I. Semenov (Научный диалог)
The relevance of the study is due to the growing interest in the study of both colloquial speech and regional linguistic phenomena. The author proceeds from the fact that the study of regional speech facts makes it possible to clarify the idea of the functioning of regional systems, taking into account various discursive restrictions. The author dwells on the interpretation of lexical meanings, description of the functioning features and methods of formation of 6 common nouns and 8 proper names, formed from the toponym “Kolyma” and included in the group of homonyms “Kolymka”. It is shown that these homonyms are mainly formed through universalization, while proper names are formed on the basis of real-life phrases that are regularly used to designate objects, and common nouns are created on the basis of free combinations of words. It is concluded that the study of the facts of regional colloquial speech allows us to observe the features of the functioning of regional vocabulary, which have not yet been studied. It will help to more accurately distinguish between local speech phenomena and the properties of the author’s manner of generating speech (for example, in the field of occasional word formation), as well as see reflection in the nominations various features of the perception of the region (in this case, Kolyma).